Bioaugmentation of anaerobic digesters treating lignocellulosic feedstock by enriched microbial consortia. Issue 7 (14th May 2018) - Ozbayram, Emine Gozde; Kleinsteuber, Sabine; Nikolausz, Marcell; Ince, Bahar; Ince, Orhan
Abstract: Three different bioaugmentation cultures enriched from natural and engineered cellulolytic environments (cow and goat rumen, a biogas reactor digesting sorghum biomass) were compared for their enhancement potential on the anaerobic digestion of wheat straw. Methane yields were determined in batch tests using the Automatic Methane Potential Test System operated for 30 days under mesophilic conditions. All cultures had positive effects on substrate degradation, and higher methane yields were observed in the bioaugmented reactors compared to control reactors set up with standard inoculum. However, the level of enhancement differed according to the type of the enrichment culture. Methane yield in batch reactors augmented with 2% cow rumen derived enrichment culture was increased by only 6%. In contrast, reactors amended with 2% goat rumen derived enrichment culture or with the bioaugmentation culture obtained from the biogas reactor digesting sorghum biomass produced 27 and 20% more methane, respectively. The highest methane yield was recorded in reactors amended with 6% goat rumen derived enrichment culture, which represented an increase by 36%. The microbial communities were quite similar at the end of the batch tests independently of the bioaugmentation sources, indicating that the introduced microbial communities of the enrichment cultures did not dominate the reactors.